“GONE NOW ARE, GONE ARE IN POLAND THE JEWISH VILLAGES". NOSTALGIC MYTH OF POLISH-JEWISH RELATIONS IN THE REGIONAL HISTORIOGRAPHY – RECONNAISSANCE - Krupa, Bartłomiej (Porównania, 2017)
The author presents the beginning of the Polish-Jewish issues in public discourse and literature in Poland in the 1920s and describes its dominant nostalgic features. Moreover, he shows how nostalgia permeated to the description of Polish-Jewish relations in the regional historiography in Poland. Next, he discusses the main features of this type of narrative including its danger. An example of such stories and their limitations, mainly hiding Polish anti-Semitism, is Jan Przedpełski’s book The Jews of Płock. Finally, the author points to the gradual overcoming of the nostalgic myth of Polish-Jewish relations in the regional historiography of the XXI century.